2008
DOI: 10.1152/japplphysiol.90494.2008
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the inhibiting effects of nasal CPAP on nonnutritive swallowing in newborn lambs

Abstract: The present study investigated the mechanism by which continuous positive airway pressure (CPAP) suppresses nonnutritive swallowing (NNS) during quiet sleep (QS) in newborn lambs. Eighteen full-term lambs were chronically instrumented and evenly distributed into three separate groups to determine the extent to which modulation of NNS may be attributed to stimulation of upper airway and/or bronchopulmonary mechanoreceptors. Six lambs were tracheotomized, six other lambs underwent a two-step bilateral intrathora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…Similarly, the present study indicates that nCPAP has no effect on NS-breathing coordination in full-term lambs. Overall, the coordination of breathing and NNS as well as NS appears to be largely unaltered by various conditions such as preterm birth (28), hypoxia (8), nCPAP, and nasal intermittent positive-pressure ventilation (33,34). Furthermore, the present results suggest that stimulation of positive pressure receptors in the upper airways by nCPAP, in likelihood with upper airway dilation, do not significantly alter NS in the neonatal period, including NS-breathing coordination.…”
Section: Effect Of Ncpap On Nutritive Swallowing-breathing Coordinationmentioning
confidence: 49%
See 2 more Smart Citations
“…Similarly, the present study indicates that nCPAP has no effect on NS-breathing coordination in full-term lambs. Overall, the coordination of breathing and NNS as well as NS appears to be largely unaltered by various conditions such as preterm birth (28), hypoxia (8), nCPAP, and nasal intermittent positive-pressure ventilation (33,34). Furthermore, the present results suggest that stimulation of positive pressure receptors in the upper airways by nCPAP, in likelihood with upper airway dilation, do not significantly alter NS in the neonatal period, including NS-breathing coordination.…”
Section: Effect Of Ncpap On Nutritive Swallowing-breathing Coordinationmentioning
confidence: 49%
“…Our previous studies (33,34) revealed that nCPAP had no systematic effect on NNS-breathing coordination in full-term lambs. Similarly, the present study indicates that nCPAP has no effect on NS-breathing coordination in full-term lambs.…”
Section: Effect Of Ncpap On Nutritive Swallowing-breathing Coordinationmentioning
confidence: 89%
See 1 more Smart Citation
“…Some progress has been made in the last years to decrease this stress, e.g. by using thoracic videosurgery instead of conventional thoracotomy Samson et al, 2008). However, we are continually committed to finding new ways to replace surgery by non-invasive instrumentation as often as possible, without decreasing the quality of recorded physiological signals.…”
Section: Surgical Chronic Instrumentation: a Special Concernmentioning
confidence: 99%
“…Our group has been actively studying the perinatal control of breathing in lambs since the late 80's, in an attempt to better understand the pathophysiology of apneas of prematurity, apparent-life threatening events and sudden infant death syndrome, with a special focus on laryngeal physiology (Praud et al, 2006;Samson et al, 2007Samson et al, , 2008St-Hilaire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%